2017
DOI: 10.33549/physiolres.933757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme Blockade, Alone or Combined With Blockade of Soluble Epoxide Hydrolase, on the Course of Congestive Heart Failure and Occurrence of Renal Dysfunction in Ren-2 Transgenic Hypertensive Rats With Aorto-Caval Fistula

Abstract: We showed recently that increasing kidney epoxyeicosatrienoic acids (EETs) by blocking soluble epoxide hydrolase (sEH), an enzyme responsible for EETs degradation, retarded the development of renal dysfunction and progression of aorto-caval fistula(ACF)-induced congestive heart failure (CHF) in Ren-2 transgenic hypertensive rats (TGR). In that study the final survival rate of untreated ACF TGR was only 14 % but increased to 41 % after sEH blockade. Here we examined if sEH inhibition added to renin-angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…The beneficial effects of the treatment, particularly on the survival rate, were more pronounced in ACF FHH rats. In addition, our results show that, in accordance with previous findings (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018), after creation of ACF the animals displayed signs of pronounced cardiac hypertrophy, involving both ventricles. Remarkably, this was associated with distinct lung congestion, indicating LV failure without signs of RV failure (no liver congestion).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The beneficial effects of the treatment, particularly on the survival rate, were more pronounced in ACF FHH rats. In addition, our results show that, in accordance with previous findings (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018), after creation of ACF the animals displayed signs of pronounced cardiac hypertrophy, involving both ventricles. Remarkably, this was associated with distinct lung congestion, indicating LV failure without signs of RV failure (no liver congestion).…”
Section: Discussionsupporting
confidence: 93%
“…Animals underwent either sham-operation or ACF creation as described above (at the week labeled -4) and were left without treatment for 4 weeks. Previous studies have shown that after this time CHF features are fully developed but the animals are still in the compensation phase (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018). At this time point (week 0) the rats were divided into the following experimental groups:…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…With respect to the heart function, TGR exhibited unchanged (Habibi et al, 2011; Ma et al, 2012; Neckář et al, 2012; Červenka et al, 2015a; Kovács et al, 2016) or slightly lower LV systolic function (Whaley-Connell et al, 2007; De Mello et al, 2013), depending on measured heart parameters and used methods. Further, it has been shown that TGR have increased mortality compared to normotensive HanSD rats when subjected to volume overload (Červenka et al, 2015a,b; Kala et al, 2018). Finally, there is a single paper dealing with the progression of post-MI CHF in TGR (Connelly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%